Dual Beam Sinusoidally Modulated Reactance Surface Antenna - Abdo-Sánchez, María Elena; Pérez Aguilar, Lorena; Martín-Guerrero, Teresa María; Camacho-Peñalosa, Carlos (My University, 2020)
In this work, a planar dual beam Sinusoidally Modulated Reactance Surface (SMRS) antenna is presented. Our method is based on the implementation of a surface impedance modulated by the superposition of two sinusoidal functions. In particular, the full process of designing a dual beam antenna that radiates at -14 and 28 off broadside at 10 GHz is described. In a second proposed structure, manipulation of the side lobe level (SLL) is achieved by varying the leakage constant along the antenna with negligible changes in the pointing directions. SLL reductions of 3.4 dB and 1.8 dB for each of the synthesised beams are obtained through full wave simulations, as well as gains 13.4 dBi and 13.6 dBi respectively. An excellent agreement between theoretical and simulated results is observed.
Keywords: Antenas; Radio-Antenas; Metasuperficies; Holografía acústica; leaky-wave antenna; metasurface; holographic method